2006
DOI: 10.1509/jmkg.70.3.120
|View full text |Cite
|
Sign up to set email alerts
|

Dual Distribution and Intangible Firm Value: Franchising in Restaurant Chains

Abstract: Dual distribution systems where firms simultaneously use vertical integration and market governance are widely used across diverse marketing contexts (e.g., restaurants, retailing, and industrial selling). A prominent example of dual distribution includes business format franchising, where firms, the franchisors, license operation of some of its units to franchisees while simultaneously owning and operating some units themselves. Despite the widespread prevalence of dual distribution, there are few insights on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
106
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 75 publications
2
106
1
2
Order By: Relevance
“…() found that franchisors gain more financially in plural forms. Srinivasan () found this only to be true for some franchisors. For certain chains, intangible value is unaffected, and small chains may even experience weaker financial performance if they also have high financial liquidity and a lasting advertising strategy (Srinivasan ).…”
Section: Results: a Framework Of Factors Related To Outcomes Of Francmentioning
confidence: 99%
See 1 more Smart Citation
“…() found that franchisors gain more financially in plural forms. Srinivasan () found this only to be true for some franchisors. For certain chains, intangible value is unaffected, and small chains may even experience weaker financial performance if they also have high financial liquidity and a lasting advertising strategy (Srinivasan ).…”
Section: Results: a Framework Of Factors Related To Outcomes Of Francmentioning
confidence: 99%
“…Srinivasan () found this only to be true for some franchisors. For certain chains, intangible value is unaffected, and small chains may even experience weaker financial performance if they also have high financial liquidity and a lasting advertising strategy (Srinivasan ). All three studies considered the same outcome, industry and country; however, the study by Srinivasan was conducted earlier and used a larger sample and study period than the study by Koh et al .…”
Section: Results: a Framework Of Factors Related To Outcomes Of Francmentioning
confidence: 99%
“…Garg (2013) focused on the drivers of differentiation, and our article complements that work by explaining the drivers of the other generic competitive advantage for MUF, low cost. Therefore, they are likely to advertise more in those marketing channels that have lower threats from free riding (Srinivasan, 2006). While the choice of industry may be one variable that explains success or failure of franchising systems (Garg, 2005a), the choice of appropriate organizational form may be another crucial variable.…”
Section: Discussionmentioning
confidence: 99%
“…Restaurant chains often serve as the empirical setting of these studies (e.g. Bradach, 1992Bradach, , 1997Sorenson & Sorenson, 2001;Srinivasan, 2006). In this article we have examined pharmacy chains rather than restaurant chains.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Sorenson & Sorenson (2001) and Srinivasan (2006), we also study the performance implications of the plural form. A distinction is made between two types of performance: the performance of chain operators (i.e.…”
Section: Introductionmentioning
confidence: 99%